DEVELOPING ENGLISH READING TEXTBOOK OF PROCEDURE TEXT FOR GRADE XI OF AVIATION MANAGEMENT VOCATIONAL SCHOOL - Dian Regina and Masitowarni Siregar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2018)
The study aims to make an appropriate English reading textbook for grade XI students of aviation management vocational school, Medan. This study was conducted by applying the six phases of educational research and development proposed by Borg and Gall which are 1) Gathering information and data, 2) Analyzing data, 3) Developing Procedure Text Materials, 4) Validating new procedure text materials by expert, 5) Revising reading procedure text materials based on experts’ suggestions, and 6) Final Products (Reading Procedure Text Textbook). It was found that students and teacher agreed that the existing materials currently used by the students were irrelevant with aviation management’s students. The irrelevance materials were then developed by applying the ESP approach. The texts were developed into five new relevant procedure text materials. The new materials were validated by two experts. The average score of the validation was 4.6. It showed that the new procedure text materials were very good, relevant, and feasible.